The Role of Kisspeptin in Intracytoplasmic Sperm Injection Cycles in a Group of Infertile Iraqi Females - Qasim, Hiba R.; Mohammed, Najeeb H. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Infertility is a global issue that not only affects individuals but also impacts society as a whole. Kisspeptin has emerged as a key player in the understanding of certain facets of infertility. However, research on the role of kisspeptin in fertility, particularly in assisted reproductive treatment, remains limited.Objectives: To investigate the potential association between follicular fluid kisspeptin levels and various reproductive parameters, including the number and maturity of oocytes, fertilization rate, pregnancy detection, anti-Müllerian hormone levels, and the age of females.Methods: Sixty infertile couples with an age range of 20 – 40 years participated in this study. They complained of unexplained infertility, had no hormonal or male factors, all with the same stimulation protocol, with follicular fluid collected on the day the oocytes were retrieved. These follicular fluid samples were centrifuged and then frozen at -20ºC until the day an enzyme-linked immunosorbent assay (ELISA) for kisspeptin was done. The study was conducted at the High Institute for Infertility Diagnosis and Assisted Reproductive Technology, Al-Nahrain University, Baghdad, between the 1st of January to the 1st of July, 2023.Results: A significant negative correlation was found between follicular kisspeptin levels and female age. Kisspeptin levels positively correlated with the number of retrieved oocytes, mature oocytes, fertilized oocytes, and AMH levels. Higher kisspeptin levels were observed in pregnant women (707.7 ± 235.28 pg/mL) than in non-pregnant ones (648.9 ± 215.27 pg/mL), but the difference was not significant. A strong positive correlation was found between follicular and serum kisspeptin.Conclusion: This study suggested that kisspeptin may play a key role in ovarian function, as its levels were associated with oocyte quality and ovarian reserve. The observed relationship between kisspeptin levels and both female age and reproductive outcomes highlights its potential as a biomarker in assisted reproduction.